Increased vitamin D intake may reduce psychological anxiety and the incidence of menstrual irregularities in female athletes - Miyamoto, M.; Hanatani, Y.; Shibuya, K. (PeerJ, 2022)
Background: Vitamin D deficiency has been associated with major depression and premenstrual mood symptoms, and menstrual irregularity has been correlated with mental anxiety. However, the potential effect of increased vitamin D intake on reducing the risk of menstrual irregularities by decreasing psychological anxiety is yet to be fully elucidated. The existence of such a relationship in athletes with high levels of psychological anxiety and adequate dietary intake remains unknown. Therefore, this study aimed to examine the effects of vitamin D intake on psychological anxiety levels and the risk of menstrual irregularities in healthy college-and international-level female athletes. Methods: Female intercollege-level track and field and international-level rowing athletes (n = 107) aged 15-24 years were included in this study. Their nutritional intake, body mass, body fat, mental anxiety, and menstrual irregularities were investigated. A generalized linear mixed model (GLMM) was used to examine the effects of several parameters on menstrual irregularities. The independent variables introduced into the GLMM were determined based on Akaike`s information criterion. Results: The GLMM identified a significant interaction effect of vitamin D intake and state anxiety on menstrual irregularities, with a p-value of 0.049 and an odds ratio of 0.423. The study results suggest that increased vitamin D intake in relatively young endurance athletes may reduce mental anxiety, consequently decreasing menstrual irregularities.